Private enforcement in Cartel cases: access to damages - Moodaliyar, Kasturi (My University, 2020)
In an open market, firms compete to win the business of their customers by offering more products or services at lower prices. Cartelists, however, by colluding with their competitors to fix higher prices at lower output, effectively transfer money out of the pockets of unsuspecting consumers into their own coffers in the form of higher profits. Because cartelists do not compete for their profits, there is little incentive for them to be efficient or to innovate. This is not only bad for consumers but ultimately harmful to the economy as a whole. To acquire any compensation for the harm done, victims of cartels have to approach the civil courts. This path to compensatory damages in competition cases is not well defined in South African jurisprudence. The competition authorities regulate a particular understanding of competition law within a public enforcement context, which has not been conveyed to the civil courts. Damages claimants face challenges related to resources and access to evidence and must navigate the court system. The focal point of this dissertation is how private enforcement can become more accessible to victims who have been harmed by cartel conduct. The current legal framework in South Africa does very little to promote private enforcement and I call for policy intervention. Using theories of damages, I explore how one could establish the cause of action between the harm done by the cartel and the injury suffered by the claimants. I conclude that there are aspects of common-law and statutory damages that may be useful for the claimants to argue their case. I assess the economic models that quantify the damages claim and conclude that the model used should be case dependent. I examine the certification criteria required for claimants to bring a class action complaint and argue that private enforcement in South Africa should not be advanced through case development in the courts alone, but that there is also a need for policy reform which I will extrapolate from the issues I have covered below. I explore the debate on whether direct and indirect purchasers should be entitled to damages, and the possibility of the cartel raising a passing-off of the overcharge defence. In doing so, I examine cases in the United States and the European Union, which have dealt extensively with this issue. I argue that in South Africa, unlike in the US, both direct and indirect purchasers should be allowed to claim damages, with some qualifications. Finally, I assert that evidence the Competition Commission obtains through its corporate leniency policy used to prosecute cartels should be shared with the damages claimant. I provide recommendations for a White Paper policy guideline which could lead to legislative intervention. In South Africa, there is more emphasis on public enforcement of cartels and perhaps it is time we strengthen the private enforcement and encourage more competition law damages cases. Damages claimants are deserving of access to justice
A thesis submitted in fulfilment of the requirements for the degree Doctor of Philosophy in the School of Law, at the University of the Witwatersrand, 2020